1988
DOI: 10.1093/nar/16.23.11057
|View full text |Cite
|
Sign up to set email alerts
|

Identification of two novel members oferbAsuperfamily by molecular cloning: the gene products of the two are highly related to each other

Abstract: Two v-erbA-related genes, named ear-2 and ear-3, have been identified in the human genome and characterized by cDNA cloning. These genes are predicted to encode proteins that are very similar in primary structure to receptors for steroid hormones or thyroid hormone (T3). In addition, amino acid sequences of the ear-2 and ear-3 gene products are very similar each other especially at the DNA binding domain (86% homology) and at the putative ligand binding domain (76% homology). Northern hybridization with ear DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
97
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(102 citation statements)
references
References 39 publications
4
97
0
Order By: Relevance
“…The first half-repeat is identical and the second very homologous to the consensus half-repeat site 5Ј-AG(G/T)TCA-3Ј of the HREs (39 -41). DNA-binding gel electrophoresis assays using extracts of COS-1 cells transiently transfected with plasmids expressing HNF-4, ARP-1 (COUP-TFII), or EAR-2 (COUP-TFI) (18,42) showed that oligonucleotide CIIC binds ARP-1 and EAR-2 but does not bind HNF-4, indicating that the region defined by footprint CIIC is an important regulatory element.…”
Section: Discussionmentioning
confidence: 99%
“…The first half-repeat is identical and the second very homologous to the consensus half-repeat site 5Ј-AG(G/T)TCA-3Ј of the HREs (39 -41). DNA-binding gel electrophoresis assays using extracts of COS-1 cells transiently transfected with plasmids expressing HNF-4, ARP-1 (COUP-TFII), or EAR-2 (COUP-TFI) (18,42) showed that oligonucleotide CIIC binds ARP-1 and EAR-2 but does not bind HNF-4, indicating that the region defined by footprint CIIC is an important regulatory element.…”
Section: Discussionmentioning
confidence: 99%
“…Unexpectedly, we isolated an ear2 sequence in a cDNA library screen that, when linked in frame to remnants of a gag sequence of the Moloney murine leukemia virus, exhibited resistance to TGF-␤-induced cell-growth inhibition (data not shown). The nuclear orphan receptor, ear2 (erbA related gene 2), is a member of the COUP-TF (NR2) subfamily of nuclear hormone receptors and shares homology with TR␣ (Miyajima et al, 1988). Whereas gag-ear2 fusion is artificially created during the construction of cDNA library, fusion proteins between a viral gag sequence and nuclear hormone receptors have been identified in nature (Grignani et al, 1998;Lin and Evans, 2000;La et al, 2003).…”
Section: V-erba Expression Dysregulates Tgf-␤ Signalingmentioning
confidence: 99%
“…We were prompted to test whether v-ErbA might disrupt TGF-␤ signal transduction activity when we isolated an ear2 sequence in a cDNA library screen that, when linked in frame to remnants of a gag sequence of the Moloney murine leukemia virus, exhibited resistance to TGF-␤-induced cell-growth inhibition. The nuclear orphan receptor, ear2 (erbA related gene 2), is a member of the COUP-TF (NR2) subfamily of nuclear hormone receptors and shares homology with TR␣ (Miyajima et al, 1988). Using retroviral gene-mediated transfer, the full-length coding sequence of v-ErbA with a C-terminal-Flag-tag was stably expressed in the mink lung epithelial cell line (PE25) that was previously modified to express an ectopic receptor and the TGF-␤-responsive PE2.1 luciferase reporter gene (Liu et al, 1997;Hua et al, 1998).…”
Section: V-erba Expression Dysregulates Tgf-␤ Signalingmentioning
confidence: 99%
“…The latter result suggests that the repression by EAR3/COUP-TF1 involves specific competition with HNF-4 for binding to the Epo gene. Since EAR3/COUP-TF1 and ARP-1/COUP-TF2 receptors are expressed in a broad variety of tissues and EAR2 is expressed primarily in the liver (33), it is likely that one or more of the COUP family members modulate the expression of Epo in vivo. As yet we have no evidence that EAR3/COUP-TF1 is a more likely contributor than other COUP family members.…”
Section: Fig 4 An Ear3/coup-tf1-related Factor From Hep3b Nuclear Ementioning
confidence: 99%